Light-Cone Gauge Strings and Quantization - Năstase, Horaţiu [UNESP] (My University, 2019)
In the previous chapter, we have described the classical theory of strings, from the point of view of their worldsheet. Here we will describe the way to quantize them, using a particular gauge called light-cone gauge.